TRANSFORMASI PEMBELAJARAN IPA MELALUI PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Eldyana Citra Laksita; Fitri Nuraeni; Tiara Yogiarni (STKIP Subang, 2025)
This study was driven by the low level of students critical thinking skills in elementary science learning, which is attributed to the continued use of conventional teaching methods that have not effectively fostered students higher order thinking. The purpose of this research is to analyze the effect of the problem based learning (PBL) model supported by augmented reality media on improving students critical thinking skills. A quantitative method was applied using a quasi-experimental design with two groups: an experimental class and a control class. A critical yhinking skills test was used as the instrument, consisting of five indicators: clarification, basis for decision-making or support, inference, further explanation, and strategy and tactics. Descriptive analysis showed that the experimental class average pre-test score was 35.14 (SD=11.491), indicating low initial understanding. After the intervantion, the post- test average increased to 54.55 (SD=11.544), showing a significant improvement of 19.41 points. Normality and homogenity tests confirmed that the data met statistical assumption. The paired sample T-test showed a significant difference between pre-test and posttest scores ( p < .001) and the N-Gain score reached 0.521 (moderate category), with an effectiveness rate of 52.1%. These results indicate that the problem based learning model assisted by augmented reality significantly enhances students critical thinking skills.